Winning the second half: The perceived and actual impact of the coach's half-time speech on basketball players' performance. Issue 5 (October 2022) - Zach, Sima; Avugos, Simcha; Bakalo-Kuffler, Liat; Bar-Eli, Michael
This study was designed to explore coaches' half-time speeches and whether players perceive these speeches as having an impact on their performance later in the game. A mixed-methods convergent design was used. Participants were nine male basketball players aged 19–34 (M = 27, SD = 4.76) from a team playing in the Israeli Basketball Premier League, as well as their head coach (aged 41) and two assistant coaches (aged 51 and 34). Data were collected on the coach's speeches at half-time in games during the regular season. In addition, face-to-face semi-structured interviews with the players and the two assistant coaches were conducted at midseason. The average speech duration was approximately 3 min, and messages were delivered at an average pace of one theme every 13 s. The most frequent theme was psychological, with more negative themes delivered compared to positive ones. Psychological themes appeared 50% more than informational. We discuss the differences in the features of the talks between games in which the team was trailing at half-time, and games in which they reached half-time with a leading score. A surprising gap exists between the participants' perception regarding the contribution of the half-time speech to players' performance, and the actual score at the end of the game.